W. Α. Heurtley, Prehistoric Macedonia . Anarchaeological reconnaissance of Greek Macedonia (West of the Struma) in the Neolithic , Bronzeand Early . Iron Ages. 40V, σελ. XXVI+275, frontispiece, εικ. 112 , πίν. 23. Cambridge University Press 1939. - Μ. Χ. (Μακεδονικά, 2017)
[χωρίς περίληψη]